Penapisan Senyawa Fitokimia dan Aktivitas Antioksidan Daun Bidara (Ziziphus Mauritiana) - Mochtar, Fransiska (Syntax Corporation, 2025)
Ziziphus mauritiana leaves have traditionally been used to treat various ailments, particularly those related to inflammation and infection. This therapeutic potential is presumed to be associated with its content of bioactive compounds exhibiting antioxidant activity. This study aimed to identify secondary metabolites and evaluate the antioxidant activity of Z. mauritiana leaf extract. Phytochemical screening was conducted using specific reagent methods, while antioxidant activity was measured using the DPPH radical scavenging assay. The results revealed the presence of alkaloids, flavonoids, steroids, tannins, and saponins, with saponins being the most abundant (89.8%). The extract also showed considerable levels of flavonoids (12.8%) and phenolics (9.72%), contributing to its antioxidant potential. The DPPH assay indicated a concentration-dependent increase in inhibition, with an IC₅₀ value of 92.58 µg/mL, suggesting moderate to strong antioxidant activity. These findings highlight the potential of Z. mauritiana leaf extract as a natural source of bioactive compounds for the development of phytopharmaceutical products.